1976
DOI: 10.1083/jcb.68.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Sorting out of normal and virus-transformed cells in cellular aggregates.

Abstract: The sorting-out behavior (self-segregation of two cell types from mixtures of the two) of five different established cell lines was studied. Eight of the ten possible binary combinations of these lines, cultured as cellular aggregates, were examined. Mouse BALB/c 3T3 cells sorted out internally to the corresponding malignant SV40 virus-transformed 3T3 cells. The transformed 3T3 line (SVT-2) did not sort out from a revertant line selected from SVT-2 cells by resistance to concanavalin A (con A). The revertant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Formation of three-dimensional cell aggregates by rotation-mediated aggregation of single cell suspensions of cultured cells has been 169 used in developmental biology for many years as a tool for studying adhesive and cognitive interaction between embryonic cells (94). More recently, aggregates prepared in this way, and the closely related three-dimensional cell spheroid system, have been used as in vitro models of tumor invasion (95,96) and infiltration of host inflammatory cells into neoplastic tissue (97). It has been argued that cell penetration into three-dimensional structures of thiskind better approximates tumor invasion in vivo than the highly simplified two-dimensional cell monolayer system.…”
Section: A Invasion Of Host Tissuesmentioning
confidence: 99%
“…Formation of three-dimensional cell aggregates by rotation-mediated aggregation of single cell suspensions of cultured cells has been 169 used in developmental biology for many years as a tool for studying adhesive and cognitive interaction between embryonic cells (94). More recently, aggregates prepared in this way, and the closely related three-dimensional cell spheroid system, have been used as in vitro models of tumor invasion (95,96) and infiltration of host inflammatory cells into neoplastic tissue (97). It has been argued that cell penetration into three-dimensional structures of thiskind better approximates tumor invasion in vivo than the highly simplified two-dimensional cell monolayer system.…”
Section: A Invasion Of Host Tissuesmentioning
confidence: 99%
“…ethylene glycol bis(#-aminoethyl ether)-NN'-tetraacetic acid (EGTA) (0.5 mM, in phosphate-buffered saline) and were formed into cellular masses or aggregates in one of two ways. Under these conditions, both cell types were previously shown to display viability comparable to the same cells maintained as confluent monolayers (11,12). One method of aggregate formation consisted of allowing 3 X 106 cells to aggregate in 3 ml of medium in 10-ml flasks on a gyratory water bath shaker as previously described (13).…”
mentioning
confidence: 99%
“…This work stimulated many other studies comparing the adhesive behavior of a variety of normal and tumorigenic cells, and of cell lines repeatedly selected for high or low metastatic capacity. In some cases, the transformed or highly metastatic cells were found to display reduced adhesiveness (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), while in other studies, the adhesiveness of these cells was increased (30)(31)(32)(33)(34). Finally, still other studies found no differences or subtle differences (35)(36)(37)(38)(39)(40).…”
Section: Cell Adhesiveness and Cancermentioning
confidence: 76%